Thermally induced instability on asymmetric buckling analysis of pinned-fixed FG-GPLRC arches. (1st January 2022) - Yang, Zhicheng; Liu, Airong; Lai, Siu-Kai; Safaei, Babak; Lv, Jiangen; Huang, Yonghui; Fu, Jiyang
Highlights: Closed-form analytical solutions for stability analysis of a pinned-fixed FG-GPLRC arch are presented. Both static and dynamic buckling modes of the arch are asymmetric. The number of limit points of the arch system would increase under a higher temperature. The number of limit points on the static equilibrium path can be directly determined. Abstract: In the present work, an analytical study on the asymmetric static and dynamic buckling of a pinned-fixed functionally graded graphene nanoplatelet reinforced composite (FG-GPLRC) arch under thermal conditions is presented. The reinforcement of graphene nanoplatelets (GPLs) is dispersed along arch thickness by following a power law distribution. Making use of the modified Halpin–Tsai micromechanical model and energy method, the static buckling load of the arch under an arbitrary radial point load and the dynamic buckling load of the arch under an arbitrary radial step point load can be derived, which could be applied to determine the existence of dynamic buckling and the phenomenon of multiple limit points under a static state. A numerical analysis is conducted to verify the accuracy of the analytical method, a good prediction on the static and dynamic buckling of the pinned-fixed FG-GPLRC arch is demonstrated. In this study, the influence of GPLs weight fraction, concentration and geometry on the static and dynamic buckling of the arch is comprehensively discussed. The dynamic and static buckling loads of the arch are found to be sensitive to applied load position under various elevated temperatures. Arch buckling load decreases as the power law index increases, but it increases as temperature rises. It is also found that the present approach is able to trace the postbuckling paths of the arch for stability analysis. Besides, accurate first-known thermal buckling solutions are also presented.